A note on conditional arbitrage-free maximum entropy densities for simulative option pricing - Klaus Herrmann (Friedrich-Alexander-Universität Erlangen-Nürnburg, Lehrstuhl für Statistik und Ökonometrie, 2009)
In this note we present a simple method to include the no-arbitrage condition into the derivation of conditional densities using the principle of maximum entropy. For the case of identically and independently distributed returns, we easily derive that the whole process estimated that way is arbitrage free. Such a process may be directly used for simulative derivation of option prices.
Keywords: 330; Maximum Entropy density; No Arbitrage Condition; Optionspreistheorie; Arbitrage Pricing; Entropie; Theorie